2015
DOI: 10.3390/ma8085240
|View full text |Cite
|
Sign up to set email alerts
|

Plant Growth Absorption Spectrum Mimicking Light Sources

Abstract: Plant factories have attracted increasing attention because they can produce fresh fruits and vegetables free from pesticides in all weather. However, the emission spectra from current light sources significantly mismatch the spectra absorbed by plants. We demonstrate a concept of using multiple broad-band as well as narrow-band solid-state lighting technologies to design plant-growth light sources. Take an organic light-emitting diode (OLED), for example; the resulting light source shows an 84% resemblance wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 43 publications
1
8
0
3
Order By: Relevance
“…However, in the past years, light emitting diodes (LEDs) have become increasingly important as a more energy efficient alternative, in particular for tomato cultivation, which requires a daily light integral of up to 25 mol m −2 d −1 (Moe et al, 2005). Furthermore, in contrast to HPS lighting, which emits dominantly yellow and orange and very little blue light (∼5%) (Terfa et al, 2013), LED lighting can be designed to meet to photosynthesis action spectrum of the crop (Jou et al, 2015). The action spectrum of tomato leaves is well known (McCree, 1971).…”
Section: Introductionmentioning
confidence: 99%
“…However, in the past years, light emitting diodes (LEDs) have become increasingly important as a more energy efficient alternative, in particular for tomato cultivation, which requires a daily light integral of up to 25 mol m −2 d −1 (Moe et al, 2005). Furthermore, in contrast to HPS lighting, which emits dominantly yellow and orange and very little blue light (∼5%) (Terfa et al, 2013), LED lighting can be designed to meet to photosynthesis action spectrum of the crop (Jou et al, 2015). The action spectrum of tomato leaves is well known (McCree, 1971).…”
Section: Introductionmentioning
confidence: 99%
“…The leaf area and number profiles, plant biomass, and Photosynthetic rate (Pn) under the as-prepared LED light treatments were examined. We suppose the absorption spectrum of fresh leaf to be the emission spectrum of ideal light10, and then evaluate the “color rendering” of as-prepared LED lights by the Pearson product-moment correlation coefficient and CIE chromaticity coordinates.…”
mentioning
confidence: 99%
“…It is understood that low quantities of light can maintain the postharvest quality of vegetables and crops by mitigating senescence, and improving phytochemical and nutrient content in several species [41,42,43]. Additionally, it was reported that the luminescence in a certain wavelength range can not only preserve vegetables but also promote plant growth [44,45,46]. Figure 6d,e displays one possible and potential application of our developed sensors in postharvest preservation.…”
Section: Resultsmentioning
confidence: 99%